On Political Stigmatization - Shishmanov, Lazar (Media and Language, 2023)
The article examines how people interact with those who are politically different and pose a „threat“ to their beliefs and positions. Before delving into the phenomenon of political stigmatization, a review of contemporary theories on the construction of political affiliation is conducted, particularly focusing on the Big Five theory. An attempt has been made to demonstrate that political affiliation is not solely the result of rational reasoning. Therefore, hatred towards the Other could not be considered a manifestation of human intelligence. The article also explores the relationship between personality and political beliefs and ideologies. Furthermore, a distinction is drawn between general stigmatization and political stigmatization.
Keywords: stigmatization; political stigmatization; Big Five; ideology; society